Multiple Seedling Development in Neem (Azadirachta Indica) - Gurudev Singh, B.; Mahadevan, N. P.; Shanthi, K.; Geetha, S.; Manimuthu, L. (Indian Forester, 1995)
Multiple seedling development from a seed was observed in Neem (Azadirachta indica) during germination studies. The results are presented in this paper.